Uji Beberapa Paket Pemupukan Dan Dolomit Terhadap Hasil Kedelai Di Lahan Rawa Pasang Surut Provinsi Jambi - Jumakir Jumakir; Endrizal Endrizal; Suyamto Suyamto (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2016)
Jumakir et al, 2016. Test of Some Packages Fertilization and Dolomite to Soybean Yield in Tidal Swamp Land Province Jambi. JLSO 5(1):86-94.The purpose of this study was to determine the performance and productivity of soybean with various package fertilization and dolomite in tidal swamp land. This assessment was conducted in tidal swamp land with potential acid sulphate soil typology and type of flood water C, Simpang Village Berbak sub District,  East Tanjung Jabung District of Jambi Province in the dry season 2013. The design used was a randomized block design (RAK) with seven treatment and seven replications with an area of 100 m2 each treatment. The assessment results based on the analysis of variance showed significant differences on growth and yield of soybean. Urea fertilizer application, Phonska, and Biofertilizer increase soybean yield 19,61% - 25,25%, while fertilizer Phonska, Dolomite, Manure and Biological Fertilizer soybean yield increased 28,07% - 31,49% compared to the fertilizer Urea and Phonska. Fertilizer application, Phonska, Dolomite, manure and biological fertilizers Soybean Plus gives the highest yield that is 1,89 t/ha.